2019
DOI: 10.3390/rs11070736
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of Soil Salinity Using UAV-Borne Hyperspectral and Satellite Multispectral Images

Abstract: Soil salinization is a global issue resulting in soil degradation, arable land loss and ecological environmental deterioration. Over the decades, multispectral and hyperspectral remote sensing have enabled efficient and cost-effective monitoring of salt-affected soils. However, the potential of hyperspectral sensors installed on an unmanned aerial vehicle (UAV) to estimate and map soil salinity has not been thoroughly explored. This study quantitatively characterized and estimated field-scale soil salinity usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 64 publications
(70 reference statements)
2
70
0
1
Order By: Relevance
“…The results of Bannari [8] illustrated that the red band yields the best ability on features of salt-affected land. Our studies also showed that the red band based on R-FD data has a high relevance to EC; that the combined bands of 2D and 3D indices are mainly concentrated at red edge, near-IR1, near-IR2 in this study site; and that the results of study are similar to peer researchers' conclusion [13,36,37]. Eventually, it found that the two-band indices and three-band indices showed better results than other single spectral bands in this study.…”
Section: Estimation Of Salt-affected Land In Arid and Semiarid Regionssupporting
confidence: 85%
“…The results of Bannari [8] illustrated that the red band yields the best ability on features of salt-affected land. Our studies also showed that the red band based on R-FD data has a high relevance to EC; that the combined bands of 2D and 3D indices are mainly concentrated at red edge, near-IR1, near-IR2 in this study site; and that the results of study are similar to peer researchers' conclusion [13,36,37]. Eventually, it found that the two-band indices and three-band indices showed better results than other single spectral bands in this study.…”
Section: Estimation Of Salt-affected Land In Arid and Semiarid Regionssupporting
confidence: 85%
“…Additionally, the chemical weathering is also a primary cause of soil salinization, during which Fe 2 O 3 is formed by the reaction of oxygen present in the atmosphere with primary Fe 2þ minerals in the soil. Moreover, the mass percentage would increase with the aggravation of weathering (Hu et al 2019). With the aggravation of soil salinization, the coverage of non-saline-resistant vegetation and surface soil moisture would decrease.…”
Section: Resultsmentioning
confidence: 99%
“…Humidity index is the third component of Landsat8 OLI images after Hat Transformation, which can reflects the humidity of soil in the study region (Hu et al 2019). The Yellow River Delta is located in the coastal area, and there is a significant difference in humidity between the coastal and inland areas (Guo et al 2019b).…”
Section: Index Selection Of the Remote Sensing Monitoring Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies indicate the higher potential for the VNIR/SWIR domain for remote sensing applications, e.g., vegetation trait estimations using wavelengths from the Red Edge to the SWIR domain [15,18,20,24,25,27,28,30,31,[64][65][66][67][68][69]. While this spectral range is available for airborne-or satellite-borne pushbroom sensing systems, for UAV platforms, only a few first studies are known [14,15].…”
Section: Discussionmentioning
confidence: 99%